2005
DOI: 10.1007/s10517-005-0236-z
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide in the A5 Region Modulates Reaction of the Respiratory Center and Blood Pressure to Hypoxia in Rats

Abstract: Hypoxia was followed by more pronounced activation of the respiratory center and pronounced hypotensive response after unilateral injection of nitric oxide synthase blocker L-NAME into the A5 region. Microinjection of exogenous nitric oxide donor sodium nitroprusside into the A5 region abolished the effect of L-NAME on hypoxia-induced changes in activity of the respiratory center and blood pressure. Bilateral transection of the vagal and sinocarotid nerves suppressed the response of the respiratory center to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…This suggestion is based on the data that multiceptive cells of A5 area regulate peripheral chemorefl ex and its sympathetic efferent pathway via activation of NO synthesis. Thus, hypoxia-induced respiratory and hypotensive response is more pronounced after blockage of NO synthesis in A5 area by microinjection of L-NAME comparing to this response before blockage [6]. Our experiments showed that NO can regulate respiratory activity via glutamate receptors in the rostral ventrolateral areas of the medulla oblongata (retrotrapezoid nucleus) in rats [5,9].…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…This suggestion is based on the data that multiceptive cells of A5 area regulate peripheral chemorefl ex and its sympathetic efferent pathway via activation of NO synthesis. Thus, hypoxia-induced respiratory and hypotensive response is more pronounced after blockage of NO synthesis in A5 area by microinjection of L-NAME comparing to this response before blockage [6]. Our experiments showed that NO can regulate respiratory activity via glutamate receptors in the rostral ventrolateral areas of the medulla oblongata (retrotrapezoid nucleus) in rats [5,9].…”
Section: Resultsmentioning
confidence: 57%
“…Hypoxia leads to an increase in fi ring rate of the phrenic nerves (FRPN) and postganglionic sympathetic nerves and relaxation of arterial smooth muscles and BP drop via vascular NO-ergic mechanism [6]. Neuronal structures of A5 area are involved into the regulation of breathing and blood circulation during hypoxia in mammals [1,7,13].…”
mentioning
confidence: 99%
“…The latencies and durations of neuronal responses in the above zone and of corresponding changes in the mass activity recorded from the phrenic nerve under conditions of hypoxic stimulation practically coincided. This fact demonstrates that peripheral О 2 -sensitive chemoreceptors serve in this case as sources of the afferent influences [1,7]. An increase in the frequency of bursts in the phrenic nerve (by 73.8 ± 1.9%, on average; Р < 0.05) and increase in the amplitude of bursts (by 20.1 ± 0.5%; Р < 0.05) corresponded to hypoxia-related activation of A5 neurons (Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Finally, respiration-related modulation of tonic electrical activity of noradrenergic neurons of zone A5 and intensification of such activity in hypoxia [1] are indicative of a possibility that these neurons interact with neurons of the respiratory center. An inhibitory tonic influence of neurons of zone A5 on the activity of neurons of the respiratory center [5][6][7] shows that, probably, cells of the corresponding brainstem nuclei are interconnected with reciprocal synaptic linkages. All the above-mentioned data agree with the concept that the activity of noradrenergic A5 neurons, which exert modulatory effects on the respiratory and sympathetic chemoreflexes [7,8], can, to a considerable extent, be determined by convergence of afferent signals of a different nature on the cells of the above zone.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is based on the fact that pontine multireceptive A5 neurons regulate peripheral chemoreflex via stimulation of NO synthesis. In particular, after blockade of NO-synthase by microinjection of L-NAME into A5 region in rats, hypoxia produces more pronounced respiratory and hypotensive reactions in comparison with those evoked before the blockade [3]. Thus, NMDA GR are involved in the synaptic mechanism of the regulation of SBP and respiration during thermal nociceptive stimulation.…”
Section: Resultsmentioning
confidence: 97%